JURNAL Analysis Of Problem Based Learning Model Assisted By Motion Graphic Video Against Student Learning Outcomes - Mahyuni Ujung (EDUCATION JOURNAL OF INDONESIA, 2021)
The purpose of this study was to analyze the effect of the video motion graphic based problem-based learning model on student learning outcomes. This research was conducted using library research methods. The data analysis technique in this research is to use documentation study technique by analyzing relevant journals or scientific articles related to the analysis of problem-based learning models assisted by video motion graphics on student learning outcomes. Based on the results of research conducted by previous researchers, it was stated that the problem based learning model assisted by video motion graphics was feasible and good for use in learning and had an effect on improving student learning outcomes. Thus, it can be ignored from the analysis that has been carried out that the problem-based learning model assisted with video motion graphics has an effect on improving student learning outcomes. Keywords: Problem Based Learning Model with Motion Graphic Video assisted, Student Learning Outcomes.